(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: Psoriasis is a common chronic cutaneous disease that seriously affects the life quality of patients. Erythema, papules, and scales are the most common clinical presentations. Staphylococcus aureus (S. aureus) is an opportunistic pathogen and commensal bacterium. Infection with S. aureus exacerbates psoriatic lesions in affected people. Staphylococcal enterotoxins (SEs) are often categorized as superantigens, which can excite significant populations of T cells. Objective: To detect S. aureus enterotoxins’ genes (sea, and seg) among patients with psoriasis. Methods: Skin swab samples from 225 individuals who enrolled in this case-control study were obtained from February 2021 to February 2022. Those individuals were divided into 3 groups; the first group comprised 75 patients with psoriasis as a patient group. The second group comprises 75 individual burn patients suspected to have a bacterial infection as a positive control. The third group comprised 75 individuals (apparently healthy people) as a negative control. The positive control group was recruited from Burns Specialized Hospital in Medical City, the negative control group was recruited from the blood donation center in Al-Imamein Al Kadhimein Medical City, and the patient group also was recruited from the dermatology consulting department. Results: Out of 225 individuals recruited in this study, there were (112) males while the female was (113) with male to female ratio of (1:1). Females’ age ranged from (7-70 years), while males’ age ranged from (5-52 years). S. aureus isolates were identified in 82 (36.44 %). The results regarding the presence of SEs gene showed that 9 out of 22 isolates of S. aureus obtained from the psoriatic patients’ group, expressed sea while 19 out of 22 isolates expressed seg. Conclusion: The most common enterotoxin distributed in S. aureus isolates of all study groups were seg, which seems to be the most enterotoxin that detect in patients with psoriasis. Keywords: Psoriasis, S. aureus, Staphylococcal enterotoxins, Sea gene, Seg gene Citation: Umayra AN, Hassan JS, Mohsen HN. Detection of Staphylococcus aureus enterotoxins’ genes (Sea and Seg) in a sample of Iraqi patients with psoriasis. Iraqi JMS. 2023; 21(2): 180-188. doi: 10.22578/IJMS.21.2.5